INFLUENCE OF DIGITAL MEDIA ON CONSUMPTION AND DISSEMINATION OF LITERATURE RESOURCES - Dr. Sapana Sharma (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
There is an increasing agreement within the field of literary studies that the interpretation and understanding of literature necessitates a consideration of its specific mode of dissemination and preservation. The aforementioned realisation can be deemed a revolutionary development in the field of literary studies. Its most noteworthy implication is the merging of literary studies and theory with media studies and theory. The fields of media studies and media theory are dedicated to examining and understanding the diverse range of media that convey information. As a result of these fields of study, the medium through which literature is conveyed is no longer viewed as secondary to the literary substance or structure, but rather as meriting examination in its own right. Moreover, the literary content and form are often significantly impacted by the modes of their dissemination and the media prevalent during their creation in a particular time and place. The manner in which literature is received can be impacted by prevailing forms of media. The present chapter initiates a discussion on the fields of media theory and media studies, exploring their inception and contemporary relevance in the industrialised world, which has been propelled by the proliferation of novel media. Subsequently, we shall examine ten instances of the correlation between media and literature across diverse historical and cultural settings.